Options for WTO negotiations on agriculture domestic support - Bellman, Christophe; Hepburn, Jonathan (2017)
This article explores various recent ideas that governments have put forward on the issue of agricultural domestic support, with a view to helping negotiators and other actors better understand how these might affect actual levels of support as well as the maximum permitted ceilings under WTO rules.